The Influence of Social Media, SEO (Search Engine Optimization), and Mobile Applications on Consumer Purchasing Decisions at PT. Udayana Bali Ambassador - Arya Wardana, Putu Gede; Putra Richadinata, Kadek Riyan; Surya Astitiani, Ni Luh Putu (Westscience Press, 2024)
Consumer behavior is changing significantly due to the development of technology and the internet, which has impacted transaction activities from conventional to online. In Indonesia, the increase in internet users has made it easier for consumers to access information and compare products before purchasing. This requires companies, including PT Udayana Bali Ambassador, to understand the influence of digital elements such as social media, SEO, and mobile applications on consumer purchasing decisions. The three digital marketing elements are essential in building consumer relationships, increasing visibility, and facilitating buying. The combination of these three strategies creates an effective digital marketing ecosystem. This research aims to analyze the influence of social media, SEO, and mobile applications on consumer purchasing decisions at PT Udayana Bali Ambassador. The research method used is quantitative and descriptive, with data collection through questionnaires distributed online to 97 respondents. Instrument tests include validity, reliability, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity. Data analysis was conducted using multiple linear regression to test the effect of independent variables on the dependent variable. The results showed that social media, SEO, and mobile applications significantly influence consumer purchasing decisions. The calculated F value in this study has exceeded the F table value, namely, 407.078> 3.092, which means that social media (X1), SEO (Search Engine Optimization) (X2), and Mobile Application (X3) simultaneously affect consumer purchasing decisions (Y). Based on this, it can be concluded that social media, SEO, and mobile applications influence consumer purchasing decisions.